Isolation of Thermophilic Bacterial from Garara Hot Spring as Antimicrobial Producer - Asih, Enda Tarni; Agustien, Anthoni; Maliza, Rita (ORGANISMS: JOURNAL OF BIOSCIENCES, 2026)
Antibiotics were essential medicines in Indonesia, and due to the high prevalence of antimicrobial resistance, new sources of antibiotic substances were urgently needed. One of the microorganisms capable of producing novel antibiotics was thermophilic bacteria. This study aims to isolate thermophilic bacteria from Garara Hot Spring that had potential as antibiotic producers. The results indicated that isolate TUA107 exhibited the strongest antimicrobial activity against Escherichia coli and Staphylococcus aureus, with inhibition zones of 6.56 mm and 7.70 mm, respectively. These findings suggested that molecular identification of thermophilic bacteria and metabolomics studies of potential antibiotic-producing isolates from Garara Hot Spring were needed to optimize their potential.